2021
DOI: 10.1111/ssm.12448
|View full text |Cite
|
Sign up to set email alerts
|

Teaching math modeling through 3D‐printing: Examining the influence of an integrative professional development

Abstract: Mathematical modeling is a critical component of the current K–12 mathematics, science, and technology and engineering (T&E) educational standards in the United States. However, mathematical modeling is often overlooked or underemphasized in integrative STEM lessons. This could be attributed to teachers’ limited content and pedagogical knowledge related to integrating mathematical modeling in integrative STEM lessons. Continual advances in technologies like 3D design and printing software and additive manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Given the siloed structure of secondary education, collaborative planning time is often limited (Kelley et al, 2020 ). Consistent with previous research, quality PD opportunities can increase teachers’ views about collaborating with other STEM teachers outside of their content area (Asempapa & Love, 2021 ; Kelley et al, 2020 ; Love & Hughes, 2022 ). The criteria for this PD opportunity, which required teachers to work as a team consisting of biology and a T&E teacher from their school district, was intentionally designed to provide a unique collaborative PD experience that teachers may not receive during the PD events organized by their school district.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Given the siloed structure of secondary education, collaborative planning time is often limited (Kelley et al, 2020 ). Consistent with previous research, quality PD opportunities can increase teachers’ views about collaborating with other STEM teachers outside of their content area (Asempapa & Love, 2021 ; Kelley et al, 2020 ; Love & Hughes, 2022 ). The criteria for this PD opportunity, which required teachers to work as a team consisting of biology and a T&E teacher from their school district, was intentionally designed to provide a unique collaborative PD experience that teachers may not receive during the PD events organized by their school district.…”
Section: Discussionsupporting
confidence: 81%
“…The criteria for this PD opportunity, which required teachers to work as a team consisting of biology and a T&E teacher from their school district, was intentionally designed to provide a unique collaborative PD experience that teachers may not receive during the PD events organized by their school district. Other purposefully planned collaborative PD opportunities like the one examined in this study have been shown to increase teachers’ knowledge of content and self-efficacy toward teaching various STEM topics (Asempapa & Love, 2021 ; Kelley et al, 2020 ; Love et al, 2022a ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Before the program, teachers conceived MM focused on epistemological and conceptual perspectives, as is reflected in the pre-test and in the initial lesson plan. Likewise, they recognized difficulties in distinguishing MM from problem solving, a fact that was also identified by [20] when developing a TPD program focused on modeling and 3D printers. Indeed, authors such as [51,52] acknowledge that there is no simple blueprint for describing and defining universal problem-solving method or modeling processes.…”
Section: Discussionmentioning
confidence: 96%
“…Ref. [20] reports that teachers face two main challenges when promoting the use of MM practices and activities in the classroom. Firstly, there seems to be misconceptions or confusion among teachers about what MM and its practices are [21,22].…”
Section: Introductionmentioning
confidence: 99%